2004
DOI: 10.1126/science.1092641
|View full text |Cite
|
Sign up to set email alerts
|

Superlattices of Iron Nanocubes Synthesized from Fe[N(SiMe 3 ) 2 ] 2

Abstract: The reaction of the metal-organic precursor Fe[N(SiMe3)2]2 with H2 in the presence of a long-chain acid and a long-chain amine in various proportions produces monodisperse zerovalent iron nanoparticles. These Fe particles display magnetic properties that match those of bulk iron as evidenced by magnetic and Mössbauer measurements. The nanoparticles adopt a cubic shape with edges of 7 nanometers and are incorporated into extended crystalline superlattices containing nanocubes in close proximity and with their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
246
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 526 publications
(257 citation statements)
references
References 20 publications
4
246
1
6
Order By: Relevance
“…Developments with aberration-corrected TEM have revolutionized our ability to characterize such species, and over recent years an astounding level of control has been developed in the synthesis of nanomaterials. Iron and iron oxide nanoparticles of all kinds of different shapes and sizes including nanorods [609], nanocubes [610][611][612], and tetrapods [613] can be created by decomposing precursors such as iron pentacarbonyl in a ternary surfactant mixture under mild thermal conditions. In Figure 101, for example, the addition of oleic acid, sodium oleate, and tetraoctylammonium bromide modified the growth rate of different facets such that cubes and octaherda were produced.…”
Section: Realistic Materialsmentioning
confidence: 99%
“…Developments with aberration-corrected TEM have revolutionized our ability to characterize such species, and over recent years an astounding level of control has been developed in the synthesis of nanomaterials. Iron and iron oxide nanoparticles of all kinds of different shapes and sizes including nanorods [609], nanocubes [610][611][612], and tetrapods [613] can be created by decomposing precursors such as iron pentacarbonyl in a ternary surfactant mixture under mild thermal conditions. In Figure 101, for example, the addition of oleic acid, sodium oleate, and tetraoctylammonium bromide modified the growth rate of different facets such that cubes and octaherda were produced.…”
Section: Realistic Materialsmentioning
confidence: 99%
“…[22][23][24][25] In previous studies, we have evidenced the interest of organometallic complexes for the preparation of metal nanoparticles of controlled size, shape and organization. [26][27][28][29][30][31][32][33] We have shown that this methodology can be extended to the synthesis of nanoparticles of metal oxides with a precise control of morphology. [34][35][36][37] which can be, in a second step, oxidized into well crystallized nanoparticles of the corresponding oxides, without coalescence.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Uniquely, the Ni(II) amide was reported to be unstable, decomposing to a black solid at room temperature. [2] The Mn, Fe, and Co silylamides are thermally stable and have proven to be valuable synthons in diverse applications, [4][5][6][7][8][9][10][11][12][13] but the unstable nature of Ni{N(SiMe3)2}2 has hindered its further use. Its instability is especially striking because several other stable, homoleptic Ni(II) amides are known.…”
mentioning
confidence: 99%